Comparison of different methods for the occlusal dentine caries diagnosis Comparação de diferentes métodos de diagnóstico da lesão de cárie oclusal em dentina - Soraya Fernandes Mestriner; Dionísio Vinha; Wilson Mestriner Junior (University of São Paulo, 2005)
The aim of this study was to compare the effectiveness of in-vitro methods for the occlusal dentine caries diagnosis. Thirty-eight sites were evaluated on third molars without macroscopic carious cavitation in adult individuals from the city of Barretos (SP), Brazil. Visual inspection (VI), endoscopic evaluation (AcuCam), visual inspection and blunt-tipped exploratory probes (Tactile), conventional bite-wing radiographs (CR), direct bite-wing digital radiograph (DR), and direct digital radiograph with contrast and brightness controled (DRbc) were used by five observers. In order to validate the data, the teeth were sectioned and histologically evaluated. The average sensitivity and specificity values of the methods were respectively:0,25 , 0,96 (VI); 0,15 , 0,92 (AcuCam); 0,17 , 0,95 (Tactile); 0,45 , 0,73 (CR); 0,33 , 0,80 (DR) and 0,35 , 0,84 (DRbc) , the effectiveness of clinical methods (VI, AcuCam and Tactile) as well as that of radiographic methods (CR, DR and DRbc) were comparatively similar. The clinical methods presented a smaller number of false-positive diagnosis than the radiographic methods. It was concluded that visual inspection is an important diagnostic method; conventional bite-wing and digital radiography aid the diagnosis and are equally efficient to diagnose carious lesions in the dentine of teeth without visible cavitation. O objetivo deste estudo foi comparar, in vitro, a efetividade de métodos de diagnóstico de lesões de cáries oclusais em dentina. Foram avaliados 38 sítios em 3º molares sem cavidades macroscópicas, de indivíduos adultos, provenientes da cidade de Barretos. Os exames inspeção visual (IV), endoscópio (AcuCam), inspeção visual e uso de sonda exploradora de ponta romba (Táctil), radiografia interproximal (RxC), radiografia digital direta (RxD), e radiografia digital direta com manipulação do contraste e brilho (Rxcb), foram realizados por 5 examinadores não calibrados. Para validação dos dados os dentes foram seccionados e avaliados histologicamente. Concluiu-se que, comparativamente, a efetividade entre os métodos clínicos foram similares, tanto quanto entre os radiográficos. Os métodos clínicos apresentaram um menor número de diagnósticos falsos positivos do que os radiográficos.